CORPORATE GOVERNANCE AND LEVERAGE ON TAX AGGRESSIVENESS: EMPIRICAL STUDY ON MINING COMPANIES IN INDONESIA - Vanesali, Laurensia; Kristanto, Ari Budi (Universitas Pendidikan Ganesha, 2020)
This study aims to investigate the effect of corporate governance and leverage towards tax aggressiveness. The research data comprises 66 firm-year obtained from 11 mining companies during 2013-2018. They were sorted using a purposive sampling method. The hypotheses were tested using multiple regression analysis. The results indicate that institutional ownership and audit committee had a positive and significant effect on tax aggressiveness, the proportion of independent commissioners and audit quality had a negative and significant effect on tax avoidance, while leverage was not considered as a determinant of tax avoidance in Indonesian manufacturing firms.